2014
DOI: 10.3748/wjg.v20.i32.11347
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-218 is upregulated in gastric cancer after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy and increases chemosensitivity to cisplatin

Abstract: Our results indicated that targeting miR-218 may provide a strategy for blocking the development of gastric cancer and reverse the multi-drug resistance of gastric cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…In addition, miR-218 has been found to modulate chemosensitivity in human gastric cancer cells [39], and restoration of miR-218 expression increases cisplatin sensitivity, and induces apoptosis, in cisplatinresistant MCF-7 cells by targeting BRCA1 [17]. We find that experimental overexpression of miR-218 in both MCF-7/A02 and CALDOX cells restores short-term sensitivity and long-term proliferation in the presence of doxorubicin and taxol.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, miR-218 has been found to modulate chemosensitivity in human gastric cancer cells [39], and restoration of miR-218 expression increases cisplatin sensitivity, and induces apoptosis, in cisplatinresistant MCF-7 cells by targeting BRCA1 [17]. We find that experimental overexpression of miR-218 in both MCF-7/A02 and CALDOX cells restores short-term sensitivity and long-term proliferation in the presence of doxorubicin and taxol.…”
Section: Discussionmentioning
confidence: 63%
“…For instance, Tie et al (2010) found that miR-218 inhibits invasion and metastasis in gastric cancer by targeting the ROBO1 receptor. Zhang et al (2014) reported that this miRNA is upregulated following cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for gastric cancer, and increases chemosensitivity to cisplatin, indicating that targeting miR-218 might provide a strategy to block the development of this illness and reverse multidrug resistance of gastric cancer cells. Their subsequent research efforts found that miR-218 levels are lower in multidrug-resistant gastric cancer cells than in chemosensitive parental cells.…”
Section: Discussionmentioning
confidence: 99%
“…Their work used miRNA microarrays to identify an 8-fold increase in miR-218 expression after CRS-HIPEC. 71 Notably, miR-218 increased the sensitivity of the gastric cancer cells to in vitro cisplatin. miR-218.…”
mentioning
confidence: 99%
“…75 While no prospective trials have been carried out, studies have indicated that measurement of serum levels of these markers in combination, can be used for preoperative staging and monitoring the effects of therapy postoperatively and after chemotherapy. 71 Additionally, Wang et al, 76 reported that an evaluation of CEA tissue staining showed good correlations with serum CEA and prognosis. Jung et al measured CEA in both serum and ascites from 119 patients with peritoneal metastasis.…”
mentioning
confidence: 99%